A sport crisis typology: establishing a pathway for future research. (2nd December 2009) - Wilson, Bradley; Stavros, Constantino; Westberg, Kate
One of the main sponsorship benefits sought by a firm is a positive effect on corporate image through the association of their brand with a sporting entity. Given the increasing incidence of crises in sport, it can be argued that the sponsorship decision may be viewed as a form of risk-taking behaviour. Drawing on the crisis management and public relations literature, this paper examines the utility of established models within the domain of sport marketing and sponsorship. Specific emphasis is given to definitional and future research issues pertaining to athlete-triggered crises. The need for research in this area is evident given the potential brand risk associated with sponsoring athletes or teams within crisis-prone sports and the limited attention on this issue in the current literature. This paper explores the relevance of some pertinent terms that are central to an established structured crisis typology such as crisis, transgression, faux pas and terrorism and concludes with a direction for future research.